Addressing english reading comprehension difficulties by Somali origin pupils in England primary schools: Using parents as resources - Shamsudin Abikar (International Journal of Education and Learning, 2021)
The question of whether classroom reading activities in primary schools in England can be solely relied on to be sufficient for English as additional language (EAL) pupils to comprehend English text was the focus of the paper. Two case studies where Somali origin EAL pupils involved in learning English reading comprehension were utilized as a springboard to develop my argument that parents are an intrinsic part of developing pupils’ English comprehension as they may constitute financially less expensive and rich resources in terms of cultural experiences. Furthermore, England’s education policy regarding EAL pupils, reading for comprehension, and factors that influence it: vocabulary knowledge, teacher -students ratio in England school and parental involvement in schools were explored to provide an answer for the question of whether only reading for comprehension activities in the classroom is enough to promote the understanding of EAL Somali origin. It was argued that only those activities are not sufficient, and there is a need for the use of parents as resources to enrich the text input, which potentially increases the comprehension skills of Somali origin EAL pupils.